Design of Wheeled Football Robot Coordination System at Base Station Using TCP / IP - Diah Arie Widhining Kusumastutie; Farrady Alif Fiolana (Muhammadiyah University, Sidoarjo, 2020)
Wheel Soccer Division, Indonesian Robot Contest is an annual competition held by the Ministry of Education. One team in this division consists of 3 robots connected in wireless communication coordinated by base station. Besides that, base station computer also connects the robots with referee computer or called Refbox (Referee Box). Refbox as server for base station computer and base station computer as server for robots. The problem arises in base station has to play double roles, as server and client. In testing had two the results of communication from the referee box to basestation and basestation to the client so the data from the referee box can be accepted by the client with a success rate of 93%.